2019
DOI: 10.4209/aaqr.2018.06.0222
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Iron-based Oxygen Carrier Supported on Alumina/Titania for Charcoal Combustion through Chemical Looping Process

Abstract: Hematite supported on alumina or alumina/titania was fabricated to serve as an oxygen carrier in the chemical looping combustion (CLC) of charcoal. The reduction rate of Fe 2 O 3 /Al 2 O 3 and Fe 2 O 3 /Al 2 O 3 /TiO 2 particles increased with the reactor inlet's CO concentration and displayed a slight effect from elevated operating temperatures. Applying the shrinking core model, the mass transfer coefficients (k g ) for the reduction of Fe 2 O 3 /Al 2 O 3 and Fe 2 O 3 /Al 2 O 3 /TiO 2 by CO were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The kinetics for the reduction Fe2O3/Al2O3 and Fe2O3/Al2O3/TiO2 by hydrogen were calculated with the shrinking core model (SCM), exercised by most researchers for the application of various oxygen carriers for chemical looping (Abad et al, 2007;Cabello et al, 2014;Abad et al, 2015;Wu and Ku, 2018;Wu and Ku, 2019), as described in Eqs. ( 13) to ( 18…”
Section: Kinetic Parameter Determination For the Reduction Of Fabricated Oxygen Carriers By Hydrogenmentioning
confidence: 99%
“…The kinetics for the reduction Fe2O3/Al2O3 and Fe2O3/Al2O3/TiO2 by hydrogen were calculated with the shrinking core model (SCM), exercised by most researchers for the application of various oxygen carriers for chemical looping (Abad et al, 2007;Cabello et al, 2014;Abad et al, 2015;Wu and Ku, 2018;Wu and Ku, 2019), as described in Eqs. ( 13) to ( 18…”
Section: Kinetic Parameter Determination For the Reduction Of Fabricated Oxygen Carriers By Hydrogenmentioning
confidence: 99%
“…Abad et al reported the reduction kinetics toward syngas of three synthetic oxygen carriers; of them, one was an iron-based material. Some studies reported the kinetics of supported iron-based oxygen carriers for chemical looping application, either in a fixed bed system , or TGA. Mendiara et al . examined the redox kinetics of an iron ore using TGA.…”
Section: Introductionmentioning
confidence: 99%